PERBANDINGAN NILAI TEKANAN DARAH, DENYUT NADI, DAN VOLUME PARU PELAKU SHALAT TAHAJUD DENGAN YANG TIDAK TAHAJUD PADA SISWA BINA SISWA SMA PLUS CISARUA, LEMBANG - Yuda Putra Disastra; Reni Farenia; A. Fauzi Yahya (PAIFORI, 2020)
Tahajud is qiyammul lail or sunnah muakad in Islam, which is both spiritual and physical practice that integrating mind and body. Tahajud regularly has been showed the improvement of neuropsychoendocrinology sistem, relaxing muscle of breathing, and might be influencing cardiovasculae function. The aim of this study was to compare the effect of tahajud on blood pressure, pulse rate, and lung volume. Observational analytic study with cross-sectional design was conducted from June – October 2013, using direct measurement to compare calues of blood pressure, pulse rate, and lung volume (forced volume capacity – FVC and forced expiratory volume in 1 second) between tahajud and non-tahajud prayers. Fourty two male students at Bina Siswa SMA Plus Cisarua, Lembang included in this study as volunteer subjects after informed consent. The result are the mean difference for pulse rate (-2,29 ± 8,69 vs 5,38 ± 0,27; p=0,001), forced volume capacity (-0,04 ± 0,27 vs 0,37 ± 0,27; p=0,012), systolic blood pressure (-2(-22,30) vs 0(-20,30); p=0,64), diastolic blood pressure (0(-20,20) vs 0(-20,20); p=0,22), and forced expiratory volume in 1 second (2,64 ± 0,64 vs 2,23 ± 0,38; p=0,22). This study concluded that tahajud regularly provided improvement in value of cardiopulmonary system especially in pulse rate and FVC.